Causes and risk factors for early death in adult patients with acute promyelocytic leukemia: a real-life experience - Heloísa Maria Farias Fontes; Júlia Peres de Freitas; José Henrique Vanderlei Oliveira; Édyla Almeida de Sousa Moraes; Eduardo Magalhães Rego; Raul Antônio Morais Melo (Hematology, Transfusion and Cell Therapy)
Introduction: Early Death (ED) remains challenging in newly diagnosed acute promyelocytic leukemia (APL), especially in developing countries. The clinical and laboratory profile at diagnosis were evaluated and causes and risk factors were investigated in adult APL patients. Method: A retrospective real-life analysis of 141 medical records was performed of patients diagnosed with APL between 2007 and 2018, whether they were treated with the IC-APL 2006 protocol or not. Risk factors were assessed by univariate and multivariate analysis. Main results: Overall, 112 patients were included in the study. ED occurred in 22.3% of cases, surpassing clinical trial reports, with non-protocol-eligible patients presenting notably higher rates (60%), potentially due to their clinical status. Hemorrhage (60%) and infection (33.3%) were the leading causes of ED. Univariate analysis associated ED to the ECOG score; white blood cell (WBC) count; body mass index; levels of hemoglobin, albumin, uric acid, and creatinine, aPTT and INR and FLT3 mutations. Multivariate analysis identified ECOG score ≥2 and elevated WBC count as independent risk factors. Conclusion: ED remains a substantial challenge in APL, especially in real-world settings with hemorrhage and infection being the leading causes. ECOG status and WBC count emerged as independent risk factors, while age and platelet count lacked a 30-day prognostic correlation. Evaluating prognostic enhancement tools in controlled trials and real-life settings is pivotal to improving APL outcomes.